Integration of renewable energy sources with smart grid - Kathiresh, M.; Subahani, A. Mahaboob; Kanagachidambaresan, G. R., 1988- (Wiley ; Scrivener Publishing, 2021)
This book starts with an overview of renewable energy technologies, smart grid technologies, energy storage systems, and covers the details of renewable energy integration with smart grid and the corresponding controls.This book provides better views on power scenario in developing countries. The requirement of the integration of smart grid along with the energy storage systems are deeply discussed to acknowledge the importance of sustainable development of smart city. The methodologies are made quite possible with the high-efficient power convertor topologies and intelligent control schemes. These control schemes are capable to provide better control with the help of machine intelligence techniques and artificial intelligence. The book also addresses the modern power convertor topologies and the corresponding control schemes for renewable energy integration with smart grid. The design and analysis of power converters that are used for grid integration of solar PV along with simulation and experimental results are illustrated. The protection aspects of the microgrid with power electronic configurations for wind energy systems are elucidated.